AD FINEM IMPERII ROMANI! STUDIES IN HONOUR OF CORIOLAN H. OPREANU - Cristian Anton Gazdac (Journal of Ancient History and Archaeology, 2015)
AD FINEM IMPERII ROMANI! Studies in Honour of Coriolan H. Opreanu, editors: Cociș, S./ Lăzărescu, V.-A./ Gui, M./ Deac D.-A., Cluj-Napoca: Mega Publishing House, 2015, 390 pp. ISBN 9786065436008.